Immune responses to Rickettsia akari infection in congenitally athymic nude mice. - Kenyon, R H (1980)
Athymic BALB/c nude mice and euthymic BALB/c mice were infected with Rickettsia akari by the intraperitoneal route. The rickettsialpox infection was terminated in euthymic mice with only two intraperitoneal injections of the antibiotic oxytetracycline, whereas prolonged treatment was necessary to terminate the infection in athymic mice. Both athymic and euthymic mice produced specific antibody, but athymic mice were still susceptible to reinfection. Killed R. akari served as a protective immunogen in euthymic, but no in athymic, mice. When spleen cells from convalescent euthymic mice were transferred to syngeneic athymic mice, recipients showed protection against challenge. This suggests that a T-cell-dependent step is generally necessary to terminate the rickettsialpox infection.